The Southeastern Librarian, Vol.34, No.04, Winter 1984 - Lucas, Linda (The Southeastern Library Association, 1984)
The Southeastern Librarian, Vol.34, No.04, Winter 1984. Periodical.
1 electronic record. 27 pages. Scanned from original document. Contents Include: Linda Lucas- Editor's Page- 95, Rebecca Bingham- From the President's Desk- 97, Michael P. Coyle- Library Cooperation and NLS Regional Libraries- 98, Maureen Harris- Nuclear Power Information from Federal Documents: Selected DOE and NRC Publications for General Library Collections- 104, SELA Chronicle- 108, Regional News- 108, Dates to Remember- 116, Index to Volume XXXIV- 117
Keywords: Periodicals | Southeastern Library Association